2019
DOI: 10.1111/tid.13227
|View full text |Cite
|
Sign up to set email alerts
|

Very early‐onset ofCryptococcus neoformansdisease following liver transplantation: Report of two cases and a review of the literature

Abstract: Cryptococcosis is the third most common invasive fungal infection following solid organ transplantation, and mortality is high. Most cases occur late and are due to reactivation of latent infection; however, very early reactivation and donor‐derived transmission can occur. Routine screening pre‐transplant and antifungal prophylaxis for cryptococcosis post‐transplant in solid organ transplantation are not standard practice. We present two cases of very early‐onset Cryptococcus neoformans disease following liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…This finding may be related to the susceptibility of liver transplant recipients to cryptococcosis during transplant candidacy. 8,9 In the present study, we reported a rare and unusual case of a liver transplant in our centers, who presented with liver mass in ultrasonography in his routine follow-up after transplantation. The liver mass biopsy revealed early cryptococcosis infection.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…This finding may be related to the susceptibility of liver transplant recipients to cryptococcosis during transplant candidacy. 8,9 In the present study, we reported a rare and unusual case of a liver transplant in our centers, who presented with liver mass in ultrasonography in his routine follow-up after transplantation. The liver mass biopsy revealed early cryptococcosis infection.…”
Section: Introductionmentioning
confidence: 62%
“…Transplanted organ involvement usually suggests transmission from the donor, and it is most common in liver transplants. This finding may be related to the susceptibility of liver transplant recipients to cryptococcosis during transplant candidacy 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…However, very early reactivation and donor-derived transmission have also been reported. In such cases, the infection generally occurs within the first month after transplantation, [15,16]. In the two cases described, infection appeared more than one year after transplantation.…”
Section: Sirmentioning
confidence: 90%
“…8 In two recently reported cases of cryptococcosis surfacing one to six days following liver transplantation, retrospective testing showed cryptococcal antigen in the serum of both patients pre-transplantation. 9 Neither of these patients was transplanted for hemochromatosis, but one had diabetes and both had cirrhosis. 9 The patient of this report had a progressive leukocytosis, starting with a WBC count of 15,500/mm3 and culminating in a leukemoid reaction with a WBC count of 57,700/cmm 3 .…”
Section: P E R H a P S T H E M O S T I M P O R T A N T C O N D I T I O Nmentioning
confidence: 99%
“…9 Neither of these patients was transplanted for hemochromatosis, but one had diabetes and both had cirrhosis. 9 The patient of this report had a progressive leukocytosis, starting with a WBC count of 15,500/mm3 and culminating in a leukemoid reaction with a WBC count of 57,700/cmm 3 . A leukemoid reaction is an elevation of peripheral blood leukocyte count into the range usually due to leukemia, variously defined as above 30,000/mm 3 , above 40,000/mm 3 or above 50,000/mm 3 .…”
Section: P E R H a P S T H E M O S T I M P O R T A N T C O N D I T I O Nmentioning
confidence: 99%